Association between arterial stiffness, cerebral small vessel disease and cognitive impairment: A systematic review and meta-analysis - van Sloten, Thomas T.; Protogerou, Athanase D.; Henry, Ronald M.A.; Schram, Miranda T.; Launer, Lenore J.; Stehouwer, Coen D.A. (Neuroscience and biobehavioral reviews, 2015)
Arterial stiffness may be a cause of cerebral small vessel disease and cognitive impairment. We therefore performed a systematic review and meta-analysis of studies on the association between stiffness, cerebral small vessel disease and cognitive impairment. For the associations between stiffness (i.e. carotid-femoral pulse wave velocity (cfPWV), brachial-ankle PWV (baPWV), carotid stiffness and pulse pressure) on the one hand and cerebral small vessel disease and cognitive impairment on the other, we identified 23 (n=15,666/20 cross-sectional; 1 longitudinal; 2 combined cross-sectional/longitudinal) and 41 studies (n=57,671/26 cross-sectional; 11 longitudinal; 4 combined cross-sectional/longitudinal), respectively. Pooled analyses of cross-sectional studies showed that greater stiffness was associated with markers of cerebral small vessel disease with odds ratios, per +1 SD, of 1.29-1.32 (P<.001). Studies on cognitive impairment could not be pooled due to large heterogeneity. Some (but not all) studies showed an association between greater stiffness and cognitive impairment, and the strength of this association was relatively weak. The present study supports the hypothesis that greater arterial stiffness is a contributor to microvascular brain disease.